Ijtihad dan Beberapa Ide Pembaruan dalam Fikih Islam. - Umar Al-Haddad (AHKAM : Jurnal Ilmu Syariah, 2016)
Assumption that the door of ijtihad was closed, despite ever becoming conspicuous in general, has never been universally accepted by all scholars. In the period after the fourth century BC /10 AD—during the opinion was evolving—history still noted the emergence of figures not only by showing their thought on ijtihad but also by showing their firm rejection to the view which said that the door of ijtihad was closed. By reviewing the position of ijtihad and its development in the history of Islamic jurisprudence (fiqh), this article proves that ijtihad is a must in the dynamics of the Islamic law. With the spirit of ijtihad, various reform ideas in Islamic jurisprudence in modern times have become possible and kept open for discourse, such as the approach between schools, collective ijtihad, ijtihad in the field of principles (ushûl) , and a review toward the qualification of mujtahid in modern times.DOI: 10.15408/ajis.v16i1.2896